'A long journey starts with a single step'—Waimakariri's journey into suicide prevention. (7th October 2012) - Lodge, Sarah
Abstract : Background: Waimakariri has a higher suicide rate than the social impact of the National average. Furthermore, social impact of the recent earthquakes has created the potential that these statistics could increase without appropriate intervention. Aim: To develop a Needs Assessment and Action Plan that is relevant, workable, sustainable and, ultimately, effective in reducing the risk and incidences of suicide. The 558 suicides reported in New Zealand last year are 'the tip of the iceberg'; with many suicides not reported as such. This issue is a reflection of the wellbeing of our communities. Waimakariri suicide statistics relate to a diverse range of demographics. With the greater proportion of suicides in the rural population, in youth and in middle-aged men; our picture is slightly different to that for the rest of New Zealand. It was important that we developed a plan that would address the wellbeing of these groups. Method: To gather specific details of those who suicide is impossible. This information is closely protected by the Coronial court. This makes it difficult to know exactly where the problem lies. To gain a clearer picture, we took an evidence-based approach and found that victims had presented with two common contributors: a lack of resilience and insufficient protective factors in their lives. Our next step was to consider how these findings could be turned into appropriate interventions. Finally, we undertook to turn our learning into a robust local plan that aligned with the seven goals in the New Zealand Suicide Prevention Strategy. Results/Outcome: Developing this project has provided an excellent platform for discussing a traditionally taboo subject.